Literature for primary school and education of republican citizens, in the «Revista de Ensino» (SP-Brazil) - 1902-1918 - Mortatti, Maria Do Rosário Longo [UNESP] (My University, 2015)
Aiming to contribute to the understanding of unexplored aspects of the history of children's literature, of the history of the teaching of reading, and of education in Brazil, this paper focuses on the section «Children's Literature» (or similar names) of the «Revista de Ensino» (Journal of Teaching), published between 1902 and 1918, by the Beneficent Association of Public Teachers of the State of São Paulo (Brazil). By analyzing the configuration of the texts published in this Section and to be used mainly in primary schools, it is concluded that the translations/adaptations, paraphrases or original texts of Brazilian or foreign authors/signers (many of them originally not aimed at children or for teaching) that were published in the Section characterize a precursor corpus within the process of the constitution of Brazilian children's literature; and this Section contributed to the dissemination, from the early decades of the twentieth century, of a conception of children's literature that oscillates between didactic and literary genres, but always articulated with the purposes of school teaching and education of the citizens, in line with the function assigned to the primary school, under a republican political project of social and cultural modernization of the Brazilian nation under construction at that time.
Keywords: Brazil; XX Century; Children's and Youth Literature; History of Education; Language Teaching; Periodical; Teachers' Organization